2012
DOI: 10.1002/stem.1213
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Superoxide Production Negatively Regulates Neural Progenitor Proliferation and Cerebral Cortical Development

Abstract: Although high amounts of reactive oxygen species (ROS) can damage cells, ROS can also play roles as second messengers, regulating diverse cellular processes. Here we report that embryonic mouse cerebral cortical neural progenitor cells (NPCs) exhibit intermittent spontaneous bursts of mitochondrial superoxide (SO) generation (mitochondrial SO flashes) that require transient opening of membrane permeability transition pores (mPTP). This quantal SO production negatively regulates NPC self-renewal. Mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 51 publications
(61 reference statements)
1
99
0
Order By: Relevance
“…A recent study showed that rapid bursts of superoxide radical anions called superoxide flashes, which are highly reactive reduced forms of molecular oxygen, were involved in regulating the self-renewal and differentiation of mouse embryonic neural progenitor cells (NPCs). Mitochondrial superoxide scavengers or mPTP inhibitors reduce the frequency of superoxide flashes and enhance NPC proliferation [82]. In contrast, increased superoxide flashes are necessary for the differentiation of mouse NPCs into cortical neurons, and inhibiting mPTP or scavenging mitochondrial ROS impairs differentiation [83].…”
Section: Figmentioning
confidence: 99%
“…A recent study showed that rapid bursts of superoxide radical anions called superoxide flashes, which are highly reactive reduced forms of molecular oxygen, were involved in regulating the self-renewal and differentiation of mouse embryonic neural progenitor cells (NPCs). Mitochondrial superoxide scavengers or mPTP inhibitors reduce the frequency of superoxide flashes and enhance NPC proliferation [82]. In contrast, increased superoxide flashes are necessary for the differentiation of mouse NPCs into cortical neurons, and inhibiting mPTP or scavenging mitochondrial ROS impairs differentiation [83].…”
Section: Figmentioning
confidence: 99%
“…A superoxide flash event is initiated with transient opening of putative mitochondrial permeability transition pore (mPTP) and requires an intact mitochondrial electron transport chain (ETC) [2]. Functionally, superoxide flashes participate in the regulation of metabolism, cell proliferation and differentiation, hyperosmotic, inflammatory and oxidative stress responses, and even in the process of aging [5][6][7][8][9][10].…”
mentioning
confidence: 99%
“…Recent studies, in which the mitochondrial ROS sensitive probe mtcpYFP was claimed to detect superoxide production, allowed characterization of the mitochondrial input in oxidative state of proliferating [48] and differentiating NSPCs [29]. It has been shown, despite the weak basal superoxide signal, cultured proliferating cortical NSPCs exhibit spontaneous burst-like generation of mitochondrial superoxide anions (superoxide flashes) without global changes in intracellular ROS levels [48].…”
Section: Mitochondria-derived Rosmentioning
confidence: 99%
“…It has been shown, despite the weak basal superoxide signal, cultured proliferating cortical NSPCs exhibit spontaneous burst-like generation of mitochondrial superoxide anions (superoxide flashes) without global changes in intracellular ROS levels [48]. The supposed superoxide oscillation requires the opening of the mitochondrial permeability transition pore (mPTP) and activity of the electron transport chain.…”
Section: Mitochondria-derived Rosmentioning
confidence: 99%